2018
DOI: 10.1159/000495173
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MicroRNA-124 Reduces Cardiomyocyte Apoptosis Following Myocardial Infarction via Targeting STAT3

Abstract: Background/Aims: MicroRNAs play an important role in regulating myocardial infarction (MI)-induced cardiac injury. MicroRNA-124 (miR-124) plays a vital role in regulating cellular proliferation, differentiation and apoptosis. Although the alteration of miR-124 was confirmed in peripheral blood of MI patients, little is known regarding the biological functions of miR-124 in cardiomyocytes. This study was designed to explore the role of miR-124 in MI and its underlying mechanisms. Methods: Real-time PCR was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…12) The inhibition of miR-124 reduces cardiomyocyte apoptosis in MI. 13) Indeed, more investigations about the function of miRNAs in MI are needed. MiR-665 serves as a novel small molecule involved in regulating the pathological process of various diseases.…”
mentioning
confidence: 99%
“…12) The inhibition of miR-124 reduces cardiomyocyte apoptosis in MI. 13) Indeed, more investigations about the function of miRNAs in MI are needed. MiR-665 serves as a novel small molecule involved in regulating the pathological process of various diseases.…”
mentioning
confidence: 99%
“…In another study, it was shown that an inflammation mediator signal transducer and activator of transcription 3 (STAT3) levels and an inflammatory enzyme extracellular‐signal‐regulated kinase phosphorylation increased and oxidative stress decreased following global reperfusion in Cybb‐deficient heart 23 . However, He et al 24 showed that inhibition of miR‐124 reduced apoptotic cell death and regulated expression levels of genes in the apoptotic pathway (Bax, caspase‐3, and Bcl‐2) via targeting STAT3 in mice model of MI and in neonatal rat ventricular myocytes with H 2 O 2 treatment. Yu et al 25 reported that silencing of Cybb expression in cardiomyocytes resulted in a decrease in hypoxia‐induced cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…22 In another study, it was shown that an inflammation mediator signal transducer and activator of transcription 3 (STAT3) levels and an inflammatory enzyme extracellular-signal-regulated kinase phosphorylation increased and oxidative stress decreased following global reperfusion in Cybbdeficient heart. 23 However, He et al 24 that Cybb was required for the activation of the protective effect of PreC in myocardial I/R models. 26 Propofol PostC, however, has been demonstrated to reduce hepatic I/R injury by inhibiting Nox following liver transplantation.…”
Section: Statisticsmentioning
confidence: 98%
“…29 For example, he and colleagues reported that inhibition of miR-124 inhibited cardiomyocytes apoptosis and protected against MI. 30 Overexpressing miR-325-3p attenuated the cardiac tissue injury and decreased the infarct size. 31 MiR199a-3p has been described to regulate the cardiac cell proliferation and inducing cardiac regeneration after MI, either when expressed by adeno-associated virus (AAV) vector 32 or directly intra-cardiac injection.…”
Section: Discussionmentioning
confidence: 99%